Saint-Simonismus als Integrationsmethode: Idee und Wirklichkeit ; Lehren für die EU - Alfred Schüller (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2006)
At the turn of the 18th century Saint-Simon und his disciples, the Saint-Simonists, developed ideas about centrally planned and directed humane societies. These ideas are still influential and are proposed by some as guiding principles for the development of an institutional structure for a peaceful united Europe. According to the constructional interventionist ideas of the Saint-Simonists, classical liberal philosophies are the root cause of many problems in society. They therefore disapprove of liberal methods of integration which rely on competitive markets such as the one successfully employed by the German Customs Union in the 19th century. Emanating from France, the ideas of the Saint-Simonists on integration have been disseminated in a wide range of variants. However, experiences of the 20th century demonstrate the disastrous failure of the Saint-Simonist concepts of integration. So far no successful alternatives to liberal methods of integration which rely on competitive markets have been developed. Never-the-less, since the second world war, French interventions, in particular, have allowed Saint-Simonist ideals to influence the process of European Integration. While the dominance of liberal methods of integration via competitive markets was initially not challenged, the wide reaching possibilities for market interventions contained in the Maastricht treaties give a clear indication of the resurgence and spread of influence of Saint-Simonist ideals since the 1990s. Should these become dominant the multicultural community of the EU member countries will be at risk to suffer from increasing in political bureaucracy and the loss of competitive performance incentives and entrepreneurial freedom. The EU would thereby mutate to an institution described by Wilhelm Röpke as a roof without a house. This article calls for a systematic readjustment of EU policies in favour of liberal methods of integration, which should reaffirm non-discriminatory competition as the leading principle of EU integration. This aims at ensuring that the EU will remain an attractive community for its citizens in the long-term.
Keywords: 330; Interventionismus; Wirtschaftsintegration; Wettbewerbspolitik; EU-Staaten; Sowjetunion